Corporate social responsibility and firm performance: The moderation of investment horizon and corporate governance - Abdul Waheed; Shahzad Hussain; Hasan Hanif; Hamid Mahmood; Qaisar Ali Malik (Cogent Business & Management, 2021)
The current study proposes an integrated theoretical frame work, to explain the moderating role of institutional investors, their investment horizon and corporate governance mechanism in the sustainability of corporate social responsibility (CSR) and firm's performance nexus. The proposed model explains how, the positive association between CSR and firm performance relationship, established on the basis of the stakeholder and corporate citizenship theories, can be further strengthened (effective monitoring hypothesis) or weakened (myopic institutions theory) by the presence of institutional investors in the firm's ownership structure and corporate governance mechanism (agency theory). The study tested the proposed model on the unbalanced sample of 327 non-financial firms listed on the Pakistan stock exchange (PSX). The study concludes that, based on the agency theory, institutional investors (as a homogeneous group) positively moderates the CSR and firm performance relationship. However, agency theory failed to explain the negative moderation of short term investment horizon institutional investors and firm performance. The study further confirms the agency role of effective corporate governance mechanism in the sustainable CSR and firm performance relationship. The current study explored some of the major theoretical contradictions in the field of corporate finance literature, which are puzzling for the practitioners and scholars.
Keywords: G32; G34; 650; institutional investors; investment horizon; agency theory; stakeholder theory; corporate citizenship theory; integrated theoretical frame work